Metropolitan planning and large urban projects: conception and mismatches of the new centralities policy in the Metropolitan Region of Belo Horizonte - Tonucci Filho, João B. M.; de Freitas, Daniel Medeiros (Pontifícia Universidade Católica de São Paulo, 2019)
In recent decades, two processes have characterized the urban policy and urban dynamics of the Metropolitan Region of Belo Horizonte (MRBH): the resumption of metropolitan planning and the greater intensity of large urban projects (LUPs). This paper critically investigates the relationships between a set of LUPs, executed and/or designed between 2000 and 2018, and the planning under construction, with emphasis on projects for centralities in the north and south vectors of MRBH. To this end, it articulates the analysis of the LUPs’ field of power with the analysis of the planning process. The conclusions highlight approximations, contradictions and mismatches between planning, the State Government and real estate capital, especially regarding the new centralities policy.